Komunikasi Harmonis Orang Tua dengan Anak - Ratnasari, Anne (FIkom Unisba, 2007)
Harmony in family communication indicates the success of communication and interaction exchange within family members. In this paper, a harmonious communication between parents and their children was reviewed through parents credibility, the use of verbal and non-verbal communication, plus parents ability to listen their children actively. By continuously added their knowledge and information concerning parenting and communication, parents could increase their credibility. Verbal message focused on I-message applying win-win solutions, combined with humor approach, helps to delivered message effectively. Meanwhile, active listening related with parents activities in giving restatement, understanding, and questioning children’s mind and feeling.